PENGARUH CAFÉ ATMOSPHERE DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS GENERASI Z COFFEE SHOP DI PANGKALPINANG - Rafli, Muhammad; Karsiningsih, Eni; Purwasih, Rati (AGROTEKSOS, 2025)
This study aims to analyze the influence of café atmosphere and service quality on customer satisfaction and consumer loyalty among Generation Z at coffee shops in Pangkalpinang City. Pangkalpinang is a center of business and educational activities, making coffee shops popular venues for gathering, studying, and socializing, especially among Generation Z. The research was conducted at twenty coffee shops across Pangkalpinang City. A quantitative approach was employed using a survey method involving 100 respondents. Data analysis was carried out using Structural Equation Modeling (SEM) with the SmartPLS software. The results showed that both café atmosphere and service quality have a positive and significant effect on customer satisfaction. Café atmosphere has a positive effect on loyalty, while service quality does not affect loyalty. Moreover, customer satisfaction does not have a significant effect on loyalty. Additionally, neither café atmosphere nor service quality has an indirect effect on loyalty through customer satisfaction.